Systemic sclerosis associated interstitial lung disease: a conceptual framework for subclinical, clinical and progressive disease. (29th September 2022) - Roofeh, David; Brown, Kevin K; Kazerooni, Ella A; Tashkin, Donald; Assassi, Shervin; Martinez, Fernando; Wells, Athol U; Raghu, Ganesh; Denton, Christopher P; Chung, Lorinda; Hoffmann-Vold, Anna-Maria; Distler, Oliver; et al.
Abstract: Objectives: To establish a framework by which experts define disease subsets in systemic sclerosis associated interstitial lung disease (SSc-ILD). Methods: A conceptual framework for subclinical, clinical and progressive ILD was provided to 83 experts, asking them to use the framework and classify actual SSc-ILD patients. Each patient profile was designed to be classified by at least four experts in terms of severity and risk of progression at baseline; progression was based on 1-year follow-up data. A consensus was reached if ≥75% of experts agreed. Experts provided information on which items were important in determining classification. Results: Forty-four experts (53%) completed the survey. Consensus was achieved on the dimensions of severity (75%, 60 of 80 profiles), risk of progression (71%, 57 of 80 profiles) and progressive ILD (60%, 24 of 40 profiles). For profiles achieving consensus, most were classified as clinical ILD (92%), low risk (54%) and stable (71%). Severity and disease progression overlapped in terms of framework items that were most influential in classifying patients (forced vital capacity, extent of lung involvement on high resolution chest CT [HRCT]); risk of progression was influenced primarily by disease duration. Conclusions: Using our proposed conceptual framework, international experts were able to achieve a consensus on classifying SSc-ILD patients along the dimensions of disease severity, risk of progression and progression over time. Experts rely on similar items when classifying disease severity and progression: a combination of spirometry and gas exchange and quantitative HRCT.